Estudio jurídico, doctrinario y de derecho comparado sobre el stealthing: una afectación a los derechos de autonomía personal y agresión sexual con consecuencias físicas y emocionales - Espinosa Piedra, Adriana Mariela (2024)
This work aims to investigate the doctrinal and legal issues surrounding the emergence of a new legal and social problem, "stealthing," also known in Spanish as the "withdrawal of the condom without consent." "This is a new practice that has become increasingly common in today's society. It involves the malicious act of removing a condom without the other person's consent during sexual relations." In addition, this immoral behavior is illegal since it violates sexual freedom, and personal and/or bodily autonomy, thus causing emotional and physical damage to the victim of this act. That's why Ecuador should consider this new practice in its criminal legislation, as it impacts the rights to sexual integrity and personal liberty enshrined in the Constitution of the Republic of Ecuador. For the development of this work of curricular integration, we have established several legal, conceptual, and doctrinal parameters to ensure its adequate development. The research encompasses not only the legal and doctrinal aspects but also the comparative law of states that have recognized this new practice as a form of sexual assault. In our fieldwork, we conducted interviews and surveys with legal professionals, including criminal lawyers and prosecutors. Through their responses, we were able to identify the issue at hand and propose a solution to clarify how stealthing violates the rights to integrity, freedom, and personal autonomy.